Early marriage is one of the causes of stunting in Bondowoso Regency - Lucy Dyah Hendrawati; Pudjio Santoso; Toetik Koesbardiati (Universitas Andalas, 2023)
This study aims to explain the factors behind the rise of early marriages in Bondowoso Regency which can be at risk of causing stunting; study the knowledge possessed by women in early marriage, reproductive health, and child-rearing; as well as conduct studies on stakeholder wars in alleviating early marriage as well as stunting. This study uses qualitative research methods with data collection techniques using in-depth interviews. The research location is in Pujer District, Bondowoso Regency. Determination of informants using purposive sampling consisted of several mothers who had stunted toddlers, village heads, clerics, to the head of the KUA Pujer District. The results of the study show that early marriage is still a risk factor that causes stunting in children. The dispensation of marriage, liking each other, arranged marriages, and avoiding adultery are the reasons why there are still early marriages here. Other factors that cause stunting apart from early marriage are knowledge, upbringing, socioeconomic conditions, and sanitation which factors that indicate stunting in Bondowoso Regency. The role of stakeholders in internalizing the community through an approach that is following their cultural characteristics plays a very important role in reducing the number of early marriages as well as stunting. However, if it is not accompanied by the efforts of the main actors to understand the impact of this early marriage, it can be indicated that stunting will still exist in Bondowoso Regency.